Copper phthalocyanine films deposited by liquid-liquid interface recrystallization technique (LLIRCT) - Patil, K. R.; Sathaye, S. D.; Hawaldar, Ranjit R.; Sathe, B. R.; Mandale, A. B.; Mitra, A. (Journal of Colloid and Interface Science, 2007)
The simple recrystallization process is innovatively used to obtain the nanoparticles of copper phthalocyanine by a simple method. Liquid-liquid interface recrystallization technique (LLIRCT) has been employed successfully to produce small sized copper phthalocyanine nanoparticles with diameter between 3-5 nm. The TEM-SAED studies revealed the formation of 3-5 nm sized with beta-phase dominated mixture of alpha and beta copper phthalocyanine nanoparticles. The XRD, SEM, and the UV-vis studies were further carried out to confirm the formation of copper phthalocyanine thin films. The cyclic voltametry (CV) studies conclude that redox reaction is totally reversible one electron transfer process. The process is attributed to Cu(II)/Cu(I) redox reaction. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: Copper phthalocyanine; cyclic voltametry; nanoparticulate films

Characterization of clay intercalated cobalt-salen catalysts for the oxidation of p-cresol - Kshirsagar, V. S.; Garade, Ajit C.; Mane, R. B.; Patil, K. R.; Yamaguchi, A.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2009)
The intercalation of cobalt-salen complexes into the interlamelar spaces of montmorillonite clay was investigated by various characterization studies. The ``neat'' cobalt-salen complex showed a weight loss at 368 degrees C while the weight loss for the corresponding intercalated complex was observed at much higher temperature of 492 degrees C due to decomposition of the complex. The thermal stabilization observed was due to the host-guest interaction of clay and metal complex and thus confirmed the intercalation. The XANES spectrum of Co(salen)-mont sample revealed the change of symmetry from the tetrahedral in plane to the octahedral structure having an axial bonding of oxygen to the cobalt, indicating that cobalt atoms in Co(salen)-mont were coordinated axially with the lattice oxygen of montmorillonite. Both XANES and EXAFS results indicated that cobalt atoms in Co(salen)-mont form two additional Co-O bonds with a bond length of 0.199 nm by the intercalation while retaining the Co-salen structure. Co-salen intercalated into the montmorillonite clay showed the highest activity for the air oxidation of p-cresol, giving 88% selectivity to the oxidation products. Effects of NaOH concentration and various solvents on the conversion and selectivity patterns also have been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cobalt-oxygen bond; Cobalt-salen; Extended X-ray absorption fine structure; Intercalation; Lattice oxygen; Montmorillonite; X-ray absorption near edge structure

Characterization of surface acid sites in tin-silicalite-1 (Sn-MFI) molecular sieve by X-ray photoelectron spectroscopy - Niphadkar, P. S.; Patil, K. R.; Joshi, P. N. (Microporous and Mesoporous Materials, 2011)
The nature, strength and density of surface acid sites in Sn-MFI molecular sieves with different Sn-content were characterized by N 1s high resolution photoelectron peak of chemisorbed pyridine in combination with pyridine-IR and TPAD. Two peaks emerged at 399.5 +/- 0.2 and 401.5 +/- 0.2 eV by deconvoluting composite N is peak were assigned to chemisorbed pyridine on weak and relatively strong Lewis acid sites, respectively. The relative percentage of strong Lewis acid sites was found to increase with the decrease of framework Sn content. A close agreement was observed between the ratios of weak Lewis acid sites to strong Lewis acid sites obtained from XPS and TPAD. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Lewis acidity; Pyridine chemisorption; SiO2/SnO2 molar ratio; Sn-MFI; XPS